ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENJUALAN JASA PENCUCIAN SEPATU DAN TAS PADA SOJI SHOES AND BAG CARE BERBASIS MOBILE - Dandi Ramasenjaya; Kundang Karsono Juman (Jurnal informasi dan komputer, 2022)
Soji Shoes and Bag Care is one of the companies engaged in shoe and bag washing services located in Central Jakarta, the Laundry Services offered are: Washing shoes and bags that are dull, yellowed, very dirty, then shoes and bags are washed clean according to customer wishes. Currently the information system provided has not been able to manage company data, marketing company services and company information, so the company is unable to reach customers and prospective customers in DKI Jakarta. In recording/entering customer data, ordering and payment requires workers to input data manually and then recap the data into Ms. Excel, changes or as required information takes a lot of time and is at risk for input errors and data loss. The method of developing information systems in this research is the Prototype Method, and to describe the problem with PIECES, then the UML diagram as a proposed system design structure uses Use Case Diagrams, Class Diagrams, Activity Diagrams and Sequence Diagrams. The programming language used is the Java language, and uses the MYSQL database. The result of this final project is the design of a mobile information system for ordering cleaning services at the Soji Shoes and Bag Care Company.